2006
DOI: 10.1029/2006gl026814
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation in methyl bromide flux from a salt marsh

Abstract: [1] Methyl bromide (CH 3 Br) is a trace gas involved in stratospheric ozone depletion with both anthropogenic and natural sources. Estimates of natural source strengths are highly uncertain. In this study, >320 highly temporally and spatially resolved measurements of CH 3 Br emissions from a salt marsh in Scotland (56°00 0 N, 2°35 0 W) were made during one year using eight static enclosures. Net emissions showed both strong seasonal and diurnal cycles. Day-today maxima in emissions were associated with sunny d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 13 publications
7
33
1
Order By: Relevance
“…However, there was no significant influence of PAR on net methyl halide fluxes from either salt marsh, during the growing season. This lack of correlation is surprising since it has been suggested that sunlight levels are important drivers for methyl halide production by plants (Dimmer et al, 2001;Manley et al, 2006;Wang et al, 2006;Drewer et al, 2006). However, separating individual effects of PAR and temperature is difficult because of their intrinsic tendency to correlate.…”
Section: Statistical Analysis Of Potential Factors Impacting Flux Magmentioning
confidence: 83%
See 3 more Smart Citations
“…However, there was no significant influence of PAR on net methyl halide fluxes from either salt marsh, during the growing season. This lack of correlation is surprising since it has been suggested that sunlight levels are important drivers for methyl halide production by plants (Dimmer et al, 2001;Manley et al, 2006;Wang et al, 2006;Drewer et al, 2006). However, separating individual effects of PAR and temperature is difficult because of their intrinsic tendency to correlate.…”
Section: Statistical Analysis Of Potential Factors Impacting Flux Magmentioning
confidence: 83%
“…Thus gaps remain in both quantification and characterisation which must be filled in order to gain a clearer picture of the current and future impact of salt marshes on atmospheric chemistry. The aim of this study was to extend considerably a previous monitoring project for CH 3 Br fluxes at Heckie's Hole salt marsh on the east coast of Scotland (Drewer et al, 2006) by including a second site at Hollands Farm salt marsh on the west coast and measurement of CH 3 Cl. Measurements were conducted for more than 2 yr at the two salt marshes, comprising more than 450 individual daytime measurements in all seasons and more than 100 diurnal measurements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5] Seasonal and diurnal trends in CH 3 Br and CH 3 Cl fluxes from non-polar ecosystems have been reported in a number of studies [e.g., Redeker et al, 2000;Rhew et al, 2002;White et al, 2005;Drewer et al, 2006;Manley et al, 2006], but there has been no consistent evidence for external parameters driving CH 3 Br or CH 3 Cl fluxes across all ecosystem types; individual studies have suggested that light [Drewer et al, 2006], temperature [Rhew et al, 2000[Rhew et al, , 2002Redeker and Cicerone, 2004], or soil pore-water saturation [Redeker and Cicerone, 2004] may affect emissions. In arctic Alaskan tundra it was found that drained sites had greater rates of CH 3 Br and CH 3 Cl uptake than flooded sites in both coastal and inland areas [Rhew et al, 2007;Teh et al, 2009], with water table depth correlating most strongly with CH 3 Cl and CH 3 Br net uptake [Teh et al, 2009].…”
Section: Introductionmentioning
confidence: 99%